EEG hybrid brain-computer interfaces: A scoping review applying an existing hybrid-BCI taxonomy and considerations for pediatric applications - Mussi, Matheus G.; Adams, Kim D. (Frontiers in Human Neuroscience, 2022)
Most hybrid brain-computer interfaces (hBCI) aim at improving the performance of single-input BCI. Many combinations are possible to configure an hBCI, such as using multiple brain input signals, different stimuli or more than one input system. Multiple studies have been done since 2010 where such interfaces have been tested and analysed. Results and conclusions are promising but little has been discussed as to what is the best approach for the peadiatric population, should they use hBCI as an assistive technology. As previous research shows, children might face greater challenges when using BCI and might benefit from less complex interfaces. Hence, in this scoping review we included 42 papers that developed hBCI systems for the purpose of control of assistive devices or communication software, and we analysed them through the lenses of potential use in clinical settings and for children. We extracted taxonomic categories proposed in previous studies to describe what kinds of interfaces have been developed. We also proposed interface characteristics that could be observed in different hBCI, such as type of target, number of targets and number of steps before selection. Then, we discussed how each of the extracted characteristics could influence on the overall complexity of the system and what might be the best options for applications for children. Effectiveness and efficiency were also collected and included on the analysis. We concluded that the least complex interfaces might involve having single brain inputs, with a sequential role of operation, visual stimuli and external inputs. Those interfaces might also use few targets from the strobic type, with one or two steps before the final selection. We hope this review can be used as a guideline for future hBCI developments and as an incentive to the design of interfaces that can also serve children.